Program Bimbingan Karir untuk Mengembangkan Kemampuan Membuat Pilihan Karir Peserta Didik - Muhibbu Abivian; Amin Budiamin; Mubiar Agustin (utile: Jurnal Kependidikan, 2019)
Abstract: The aims of this study is to earn an effective career guidance program in increasing students career choice abilityfor 10th-grade students in 14 Senior High School. The approach of this study used in quantitative with quasi-experimentmethods and nonequivalent pretest-postest control group design as a research design. The research instrument is the on-test model which used ratting scale questionnaire. Parametric statistic was used as a technique of data analysis to measure paired sample t test. This study shows: 1) the general profile of students career choice ability; 2) the formula of suitable for career guidance program according to expert and practitioner; and 3) the effectiveness of career guidance program to increase students career choice ability.Key words: Program of Career Guidance, Career Choice ability